Peningkatan Kinerja Aparatur Melalui Sistem Informasi Short Message Services (Sms) Gateway Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Makassar - Pratama Putra, Muhammad Amril; Latifa Dinar , Sarah; Taufik, Ahmad (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2023)
This study aims (a) to determine the increase in apparatus performance through the information system Short Message Services (SMS) gateway at the Makassar City Investment and One-Stop Service Office, (b) to determine the factors supporting and hindering the improvement of apparatus performance through the Short Message information system Services (SMS) gateway at the Makassar City Investment and One-Stop Service Office. This type of research is qualitative. The data sources used are primary data and secondary data. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are reduction, data presentation, and conclusion. The results of the study show that a) Productivity of the apparatus through the SMS gateway information system at the Investment and One-Stop Service Office of Makassar City is still not fast enough in processing community SMS data services to issuing data, Inspectorate Apparatuses in Bandung Regency are still not able to operate computers, especially the use of SMS gateways. b) The quality of apparatus service through the SMS gateway information system at the Makassar City Investment and One-Stop Service Office is quite good, but there is still a lack of education and training of employees in using the SMS gateway. c) The responsiveness of the apparatus through the SMS gateway information system at the Makassar City Investment and One-Stop Service Office is quite good, every time there are complaints and complaints from the public they are always responded to quickly. d) The responsibility of the apparatus through the SMS gateway information system at the Makassar City Investment and One-Stop Service Office is in accordance with the applicable rules or norms. e) Apparatus accountability through the SMS gateway information system at the Makassar City Investment and One-Stop Services Service can already be accounted for and has been implemented properly through the performance of public services